Effect of Language Learning Apps on Vocabulary Acquisition in South Africa - Dlamini, Andile (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the effect of language learning apps on vocabulary acquisition in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The effect of language learning apps on vocabulary acquisition in South Africa indicate that these digital tools significantly enhance learners' vocabulary skills. Research shows that students who regularly used language learning apps demonstrated a notable improvement in their vocabulary acquisition compared to those who relied on traditional methods. The interactive features of these apps, such as gamified learning and spaced repetition, contributed to increased engagement and retention of new words. Additionally, learners reported higher motivation levels and a greater sense of autonomy in their language studies. Unique Contribution to Theory, Practice and Policy: Constructivist learning theory, cognitive load theory & second language acquisition (SLA) theory may be used to anchor future studies on the effect of language learning apps on vocabulary acquisition in South Africa. Educational institutions should collaborate with app developers to ensure that language learning apps incorporate these theories. Policymakers should encourage the adoption of evidence-based design principles in the development of educational technology by providing funding and resources for research in this area.